Comparison of Parenting Styles of Parents with Children 6 to 12 Years Old with and without Attention Deficit Hyperactivity Disorder (ADHD) - Morshedzadeh, Razieh; Kiyoumarsi, Firoz; Zabihi, Rozita (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2020)
Background and Aim: This study was aimed to investigate the role of emotional intelligence and positive thoughts of parents in the level of social anxiety in adolescent girls in Tehran.  Methods: This study is descriptive correlational. And the statistical population of female high school students in east of Tehran that were studying in the academic year of 2016-2017 was selected in the form of multi-stage cluster random sampling. And four girl's high schools were selected from the girl's high schools of the east, and a sample of 400 people was randomly selected. And the questionnaires of Schutte's Emotional Intelligence (1998), Positive Thinking Green et al (2004), and Liebowitz Social Anxiety Scale (1987) were administered. Data were analyzed using correlation and regression coefficients. Results:  The results showed that there is a positive and significant relationship between positive thinking score and total emotional intelligence score and emotional evaluation subscale (P=0.01), Also, there is a significant negative relationship between social anxiety and the total score of emotional intelligence and positive thinking (P=0.01); Also, emotional intelligence and positive thinking have been able to significantly predict social anxiety (P=0.01).  Conclusion: The results indicated that high levels of emotional intelligence and mothers' positive thoughts increases social anxiety in adolescent girls.